Electronegativity of Molecules Through Charge Capacity - Mala Dutta, Ms. (Asian Journal of Chemistry, 2010)
The advent of Density Functional Theory (DFT) has substantiated the insight of electronic structure in atoms and molecules. The most important of these properties are electronegativity and hardness. Few years back, Politzer had stated that electronegativity of an atom in a molecule is a polynomial function. This equation converged when the charge transfer gets equalized between the combining atoms. The present work is devoted to the determination of electronegativity of the molecules and a comparison is made with the geometric mean method used by Mulliken. Furthermore, the Gordy's electronegativity scale is tested by using the effective nuclear charge (Zeff) through ionization potential rather than Slater's rule of effective nuclear charge. In my earlier work, Zeff has been successfully used to calculate dipole polarizability of Na-clusters.